Theories in the Light of Contingency and Change: Possible Future Worlds and Well-Grounded Hope as a Supplement to Truth - Frank, Ulrich (Proceedings of the 50th Hawaii International Conference on System Sciences (HICSS-50), 2017)
Based on a critical account of the dominant concept of theory, the paper presents an alterna-tive, wider notion of theory. It is motivated by the need to cope with a contingent research subject and the assumption that IS should provide an orientation for managing the digital transfor-mation. Unlike neo-positivistic notions of theory, the proposed conception is not restricted to de-scriptions of the factual, but may be aimed at de-signing possible future worlds. Conceiving of possible future worlds requires overcoming the barriers created by language that constitutes our idea of the present world. The paper discusses the resulting methodological challenges and outlines how they might be addressed.